Analisis Genetik Objektif Afektif atas Alquran dan Terjemahnya dalam Bahasa Jawa Banyumasan - Siswoyo Aris Munandar; Laelatul Barokah; Elia Malikhaturrahmah (JOURNAL OF QUR'AN AND HADITH STUDIES, 2020)
The focus of the study conducted by the researcher this time is on the translator section, the product, and the public's response to the translation. As for the translator, the writer terms it with the genetic aspect, the researcher's product is the objective aspect, while the response of the research community is termed the affective aspect. So that the problem formulations built by the researcher include (1) How is the method of translating the Qur'an and its translation: Javanese Banyumasan?, (2) What is the quality of the translation of the Al-Qur'an and its translation: Javanese Banyumasan ?, (3) How Banyumas community response with the presence of the Qur’an and its translation: Javanese Banyumasan ?. The results of this study are; First, related to the method, this translation is a type of tafsiriah translation or communicative translation. The Banyumas language, which basically does not recognize upload-upload or karmic system, is feared that it will damage the sacred and trenendental nuances of the Qur’an, therefore the translator uses a compromise decision, namely the Banyumas language which adapts ethics. Second, related to the quality of the translation, this translation falls into the fair category. The trend used in this translation is domestication. Third, regarding the public's response to this translation, many have chosen an "easy" level of readability, meaning that the level of acceptance in the community is also "accepted".